The Impact of the Sri Lankan Civil War on the Stock Market Performances - Jayakody, Shashitha (2010)
The main focus of this paper is to study the impact of terrorist attacks on the stock market performances. The study examines nine terrorist attacks that took place during the last phase of Sri Lankan civil war, using an event study approach to analyze the efficiency of stock price reaction towards such attacks. The market model is used to examine the impact of terrorist attacks on the overall market performances while the mean adjusted returns model is employed to examine whether the 19 industries categorized in the Colombo Stock Exchange exhibit varied reactions for terrorist attacks. The results indicate that out of the nine attacks, five caused the stocks to experience statistically significant negative abnormal returns on the day of the event. The results also indicate that the impact of each individual terrorist attack varies according to the industry and type of attack.